2018
DOI: 10.1152/ajpregu.00036.2018
|View full text |Cite
|
Sign up to set email alerts
|

Models of intermittent hypoxia and obstructive sleep apnea: molecular pathways and their contribution to cancer

Abstract: Obstructive sleep apnea (OSA) is common and linked to a variety of poor health outcomes. A key modulator of this disease is nocturnal intermittent hypoxia. There is striking epidemiological evidence that patients with OSA have higher rates of cancer and cancer mortality. Small-animal models demonstrate an important role for systemic intermittent hypoxia in tumor growth and metastasis, yet the underlying mechanisms are poorly understood. Emerging data indicate that intermittent hypoxia activates the hypoxic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 167 publications
1
109
0
1
Order By: Relevance
“…The first one is the pO 2 used in the study. Indeed, in human healthy tissue, the physiological normoxia is comprised mostly between 4% O 2 (muscle) and 9.5% O 2 (kidney, outer cortex) 46,47 . In this study, normoxia and the cyH reoxygenation were performed by exposing cells to atmospheric air (21% O 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is the pO 2 used in the study. Indeed, in human healthy tissue, the physiological normoxia is comprised mostly between 4% O 2 (muscle) and 9.5% O 2 (kidney, outer cortex) 46,47 . In this study, normoxia and the cyH reoxygenation were performed by exposing cells to atmospheric air (21% O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, normoxia and the cyH reoxygenation were performed by exposing cells to atmospheric air (21% O 2 ). Nonetheless, the hypoxia value that we used was physiologically relevant since O 2 saturation in tumor is comprised between 1 and 2% O 2 in a majority of solid tumors 38,47 . Secondly, we showed that cyH induced a pro-inflammatory phenotype in M0 and M1 macrophages in both BMDM and THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…While some models employ only single cell type spheroids (146), more complex platforms, reflecting physiological interactions found in vivo include multiple cell types in a 3D structure, such as cancer stromal or endothelial cells (147,148) as reviewed earlier (149). For example, a study investigating the role of OSA in cancer employed a 3D cell culture model comprising both tumor spheroids and patient-derived monocytes subjected to IH and found that the monocyte-induced HIF-1α-dependent production of VEGF promoted tumor growth (150), providing some molecular insights into the link between the two diseases (151).…”
Section: D Cell Culturesmentioning
confidence: 99%
“…Hypoxia can result in many severe complications such as the impairment of the lung and heart, as well as certain immune system disorders, including asthma and allergic rhinitis (Davies, Bishopp, Wharton, Turner, & Mansur, 2019; Gadi, Wali, & Koshak, 2017; Kukwa et al., 2018; Ramos, Nader, & Meira, 2019). In instances such as these, hypoxia is often considered to be the primary clinical symptom of OSA, which needs to be solved first (Dewan, Nieto, & Somers, 2015; Hunyor & Cook, 2018). However, OSA related to mild upper airway obstruction can remain untreated if hypoxia can be compromised by mouth breathing, which means that mouth breathing allows the blood oxygen content to stabilize (Chowanetz, Schott, & Jany, 1987).…”
Section: Introductionmentioning
confidence: 99%